A longitudinal study using parental cognitions based on the theory of planned behavior to predict childhood influenza vaccination - Anise M.S. Wu; Joseph T.F. Lau; Yee-ling Ma; Kit-Man Cheng; Mason M.C. Lau (Elsevier, 2020)
Background: The World Health Organization recommends young children aged 6-59 months receive influenza vaccination (IV) annually. This study investigated the IV incidence in a 12-month follow-up period among 24-59 month-old children and identified its predictors based on the theory of planned behavior (TPB). Methods: A population-based random telephone survey was conducted at baseline (March-June 2011) among Chinese parents of 24-59 month-old children in Hong Kong, China, and a follow-up survey was conducted 12 months afterwards (N = 440). Results: The IV prevalence was 63.2% at follow-up (3% increased from baseline). The IV incidence during the follow-up period for all sampled, ever-vaccinated, and never-vaccinated children was 35.6, 58.5, and 7.7 per 100 person-years, respectively. Stratified analyses of logistic regression were performed for the ever-vaccinated and never-vaccinated children. After adjusting for significant socio-demographic variable(s), parental positive attitude, norm, and behavioral intention were significant predictors of IV at follow-up among ever-vaccinated children, while intention was the only significant predictor among never-vaccinated children. Conclusions: Most of the IVs received during the follow-up period were re-vaccinations rather than first-time vaccinations. Efforts should target never-vaccinated children's parents, who reported low incidence and intention. TPB also worked less well among never-vaccinated children, and thus research for other predictors of never-vaccinated children's first-time vaccination are warranted. Promotion programs should consider segmentation by children's prior vaccination status.